MEDIA MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN APLIKASI LECTORA INSPIRE MATA KULIAH PEMBELAJARAN MIKRO - Jum Dapi Okta; Yelmi Yunarti; Joko Kuswanto; Johan Eka Wijaya; Arief Qosim (JURNAL ILMIAH BETRIK, 2023)
Learning media is used to channel messages from the sender to the recipient, stimulating the thoughts, feelings, attention, and interests of students as well as their will. In this way, the learning process takes place effectively and the learning objectives are achieved. Diversified learning media has increased the diversity of students’ abilities and will provide more messages or learning resources to students, which in turn will affect their learning performance. Interactive media is one way that can help students learn better. This allows students to better understand how educators teach them. The use of interactive media is very beneficial for both parties, teachers and students. One of the courses is micro learning, which trains prospective teachers. Lectora Inspire is a media application that can be used for research and development. (R&D). The ADDIE method is used together with data collection strategies. Learn to be more effective and efficient with product validity test results in good categories.